Thinking Profile Of Junior High School Students In Understanding The Concept Of Quadrangles With Linguistic Intelligence, Logical-Mathematical Intelligence, And Visual-Spatial Intelligence - Safarudin, Yanuar Mahfudz (Professorline, 2024)
This study aims to describe the thinking profile of junior high school students who understand the concept of quadrilaterals with linguistic, logical, mathematical, and visual-spatial intelligence. This research is a descriptive study with a qualitative approach. The research subjects are three seventh-grade students of MTs Misykat Al-Anwar Kwaron, Diwek, Jombang, East Java. The research began by determining the research subjects using the MIR ( Multiple et al.) instrument. Relatively similar mathematical abilities and the same gender were also considerations for researchers when choosing subjects. Based on the interview guidelines, the researcher interviewed each subject. Data validity checking used time triangulation. Based on the results of the research that has been conducted, it was found that, (i) students with linguistic intelligence when associating information in grouping quadrilaterals based on alphabetical order, and when associating or connecting information in mentioning the properties of the flat shapes, the students pay attention to the sides first even though what is mentioned is different, such as having four sides, opposite sides are the same length, opposite sides are parallel, and when mentioning the definition of the flat shapes, the students use the genetic definition, (ii) students with logical-mathematical intelligence when associating information in grouping quadrilaterals based on simple images according to them, namely starting from rectangles, squares, then the next one is random, and when associating information in mentioning the properties of quadrilaterals, the students consistently start by paying attention to the number of sides, and continue with the following property, when associating information in mentioning the definition, the students mention the properties mentioned before by starting with the word